Plant homeodomain finger protein 2 as a novel IKAROS target in acute lymphoblastic leukemia. (January 2018) - Ge, Zheng; Gu, Yan; Han, Qi; Sloane, Justin; Ge, Qinyu; Gao, Goufeng; Ma, Jinlong; Song, Huihui; Hu, Jiaojiao; Chen, Baoan; Dovat, Sinisa; Song, Chunhua
Aim: Clinical significance of plant homeodomain finger 2 ( PHF2 ) expressions is explored in acute lymphoblastic leukemia (ALL) patients.Methods: mRNA level was examined by qPCR. The retroviral gene expression, shRNA knockdown and chromatin-immunoprecipitation are used to observe IKAROS regulation on PHF2 transcription.Results: PHF2 expression is significantly reduced in subsets of ALL patients, and PHF2 low expression correlates with leukemia cell proliferation and an elevation of several poor prognostic markers in B-cell ALL. IKAROS directly promotes PHF2 expression and patients with IKAROS deletion have significantly lower PHF2 expression. Casein kinase II (CK2) inhibitor significantly promotes PHF2 expression in an IKAROS-dependent manner, and casein kinase II inhibitor treatment also results in an increase of PHF2 expression and enrichment of IKAROS and H3K4me3 at PHF2 promoter in primary cells.Conclusion: Our results demonstrate that the IKAROS promotes PHF2 expression, and suggest that PHF2 low expression works with the IKAROS gene deletion to drive oncogenesis of ALL.